Evaluating ascent condition during the formation of 723 CE vulcanian eruption of Kelud: Implication for hazard - Jananda Nuralam Indriyanto (OPHIOLITE: Jurnal Geologi Terapan, 2025)
The 723 CE eruption of Kelud volcano in East Java, Indonesia, provides critical insights into the ascent dynamics and pre-eruptive conditions of explosive vulcanian eruption. This study examines textural and compositional variations in the groundmass and microlite morphologies of lithic-rich pyroclastic density currents (PDCs) and pumice fallout deposits from the different stages of the 723 CE eruption. Petrographic and geochemical analyses reveal contrasting ascent conditions between different clast types and eruptive stages. Lithic clasts, dominated by euhedral microlites and evolved rhyolitic groundmass compositions, crystallized under slow magma ascent and limited degassing within a dense plug or lava dome. In contrast, pumice clasts, characterized by skeletal microlites and dacitic groundmass compositions, reflect rapid magma ascent and fragmentation during explosive eruption phases. These findings highlight the dynamic interplay of crystallization, degassing, and conduit processes that govern vulcanian eruptions, particularly at Kelud. This study underscores the importance of petrological approaches in analyzing the eruptive products of vulcanian eruptions to better understand the magmatic processes responsible for such events and to improve hazard assessments for future similar eruptions.